Csiky Lajos hosszabb terjedelmű műveinek korabeli fogadtatása - TÁRKÁNYI, István-Attila (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2021)
The Contemporary Reception of Lajos Csiky’s Voluminous Works. Lajos Csiky (1852–1925) was a late 19th and early 20th-century professor of practical theology at the Theological Academy of Debrecen. His works have not yet been researched accordingly. In the first part of this short paper, we would like to present the socio-theological context in which the renowned theologian spent his creative years, focusing especially on the debate of the day between liberal and orthodox theology. In the second part, we would like to reflect on the way his major theological works were received by his contemporaries during a span of more than four decades of academic activity.